Pengaruh Social Media Influencer Dan Brand Attitude Terhadap Purchase Intention (Studi Pada Produk Emina Di Kota Semarang) - Lucky Aprilliani; Ajeng Aquinia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The business industry is growing rapidly with the emergence of various products to meet the needs of consumers who are increasingly selective in their choices. Companies need to understand consumer needs to increase product purchase intentions. This research evaluates the impact of social media influencers and brand attitude on purchase intention for Emina products in Semarang City, utilizing a questionnaire as a data collection tool, namely by applying a quantitative method where the questionnaire is filled by respondents who use and know Emina products. A total of 100 respondents were selected from the same population using the purposive sampling method. Data analysis was carried out via Multiple Linier Regression. The results of this research show that social media influencers have no effect on purchase intention because it is not significant. Meanwhile, brand attitude has a positive and significant effect on purchase intention. Keywords : Social Media Influencer, Brand Attitude, Purchase Intention